2019
DOI: 10.1002/met.1852
|View full text |Cite
|
Sign up to set email alerts
|

Correction model for rainfall forecasts using the LSTM with multiple meteorological factors

Abstract: The goal of this study was to improve the accuracy of model forecasting, such that forecasters could use model products to make more efficient daily weather predictions. Historical data of the 12 hr following a given time for various meteorological factors from the control forecasts of the European Centre for Medium‐Range Weather Forecasting (ECMWF) between 20 ° and 40 ° N latitude and 110 °–130 ° E longitude were used to verify the performance of the proposed method. Eight major meteorological factors were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…The special feature of LSTMs compared to the traditional RNNs is that they can learn to predict data in a sequence without losing important information. A few studies have demonstrated the superior performance of the LSTMs for hydrological forecasts in comparison with other ANNs (e.g., [31][32][33][34][35]). Nguyen and Bae [36] applied LSTM recurrent networks during post-processing to improve the mean areal precipitation (MAP) forecasts from the MAPLE system.…”
Section: Introductionmentioning
confidence: 99%
“…The special feature of LSTMs compared to the traditional RNNs is that they can learn to predict data in a sequence without losing important information. A few studies have demonstrated the superior performance of the LSTMs for hydrological forecasts in comparison with other ANNs (e.g., [31][32][33][34][35]). Nguyen and Bae [36] applied LSTM recurrent networks during post-processing to improve the mean areal precipitation (MAP) forecasts from the MAPLE system.…”
Section: Introductionmentioning
confidence: 99%
“…We use receiver operating characteristics (ROC) and TS (W. Woo & Wong, 2017;Zhang et al, 2019) were used. The RMSE instead of MAE was used because RMSE is more popular for precipitation forecast evaluation and is better for the evaluation of comprehensive performance.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Precipitation forecasting depends on many parameters such as temperature, pressure, humidity, wind direction, and wind speed. Due to precipitation's complexity and the uncertainty of NWP, the forecast bias cannot be ignored, especially for heavy precipitation and rainstorms (Shu et al, 2018;Zhang et al, 2019). To compensate for that, a recently developed precipitation forecast bias correction tool was produced by the European Flood Awareness System (EFAS) to improve river discharge forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…It is then not surprising that the LSTM would gain a lot of attention as a method for time series modeling [44,45,46,47,48,49,50]. For precipitation forecasting, many works have applied LSTMs to local meteorological data [51,52,53,54,55,56] and high-dimensional data such as those from radar or satellite [15,57,58,59]. On a related note, there have also been recent developments in other RNN-inspired time series models, such as Echo State Network [60,61,62], Temporal Convolutional Network [63] and Longand Short-term Time-series Network [64].…”
Section: Introductionmentioning
confidence: 99%